Fabrication and characterization of poly(octanediol citrate)/gallium-containing bioglass microcomposite scaffolds - Zeimaran, Ehsan; Pourshahrestani, Sara; Pingguan-Murphy, Belinda; Kadri, Nahrizul Adib; Rothan, Hussin A.; Yusof, Rohana; Towler, Mark Robert; Djordjevic, Ivan (Kluwer (now part of Springer), 2015)
Bone can be affected by osteosarcomae requiring surgical excision of the tumor as part of the treatment regime. Complete removal of cancerous cells is difficult and conventionally requires the removal of a margin of safety around the tumor to offer improved patient prognosis. This work considers a novel series of composite scaffolds based on poly(octanediol citrate) (POC) impregnated with gallium-based bioglass microparticles for possible incorporation into bone following tumor removal. The objective of this research was to fabricate and characterize these scaffolds and subsequently report on their mechanical and biological properties. The porous microcomposite scaffolds with various concentrations of bioglass (10, 20, 30 wt) incorporated were fabricated using a salt leaching technique. The scaffolds exhibited compression modulus in the range of 0.3-7 MPa. The addition of bioglass increased the mechanical properties even though porosity increased. Furthermore, increasing the concentration of bioglass had a significant influence on glass transition temperature from 2.5 A degrees C for the pure polymer to around 25 A degrees C for 30 bioglass-containing composite. The ion release study revealed that composites containing 10 bioglass had the highest ion release ratio after 28 days of soaking in phosphate buffered saline. The interaction of bioglass phase with POC led to the formation of additional ionic crosslinks aside from covalent crosslinks which further resulted in increased stiffness and decreased weight loss. The osteoblast cells were well attached and growth on composites and collagen synthesis increased particularly with the 10 bioglass concentration.